The effect of shipping connectivity on seaborne containerised export flows - del Rosal, Ignacio; Moura, Ticiana Grecco Zanon (Transport policy, 2022)
Transport connectivity has increasing importance in the global economy. Using a gravity equation model, this paper investigates the effect of liner shipping connectivity on seaborne containerised exports. We use a dataset from the European Comext database that includes information about the transport mode and use of containers for trade flows between EU and non-EU countries. Measuring the dependent variable with the required accuracy and addressing the potential reverse causality between trade flows and shipping connectivity, we document a positive effect of liner shipping connectivity on seaborne containerised exports and a negative effect on seaborne non-containerised ones. The results of this paper support the policy recommendations of international institutions in terms of incentivizing liner shipping connectivity. •We addressed the reverse causality between liner shipping connectivity and trade.•The higher shipping connectivity is, the lower the share of non-containerised flows.•Improving shipping connectivity may be crucial for remote countries.•Reverse causality is an issue when analysing transportation channels.